2023
DOI: 10.1002/eji.202149499
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells in the skin and oral mucosa: Brothers in arms?

Abstract: The skin and the oral mucosa represent interfaces to the environment that are constantly exposed to pathogens and harmless foreign antigens such as commensal bacteria. Both barrier organs share the presence of Langerhans cells (LC), distinctive members of the heterogeneous family of antigen‐presenting dendritic cells (DC) that have the unique ability to promote tolerogenic as well as inflammatory immune responses. While skin LC have been extensively studied in the past decades, less is known about the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 116 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…Langerhans cells, especially those in an immature state, are more likely to instruct inflammatory responses upon migration to lymph nodes [ 62 , 63 , 64 , 65 , 66 , 96 , 97 , 98 ]. We then evaluated whether fluorescein-sensitized Langerhans’ cells traveled to lymph nodes in greater numbers and/or at accelerated rates in 60-day-old BE mice when compared to their S counterparts, since reduced migration of these cells downsizes the contact hypersensitivity response [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Langerhans cells, especially those in an immature state, are more likely to instruct inflammatory responses upon migration to lymph nodes [ 62 , 63 , 64 , 65 , 66 , 96 , 97 , 98 ]. We then evaluated whether fluorescein-sensitized Langerhans’ cells traveled to lymph nodes in greater numbers and/or at accelerated rates in 60-day-old BE mice when compared to their S counterparts, since reduced migration of these cells downsizes the contact hypersensitivity response [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…This cyclic process not only keeps the mucosa balanced but also expels colonizing microorganisms. The oral mucosa primarily serves as an impermeable mechanical barrier, preventing most microorganisms from infiltrating the deeper tissues (Brand et al., 2023). The continual generation of fresh cells maintains a homeostatic equilibrium within the mucosa, and the simultaneous removal of exfoliated cells aids in the expulsion of oral microorganisms (Ptasiewicz et al., 2022).…”
Section: The Roles Of Three Components In the Oral–microbiota–brain Axismentioning
confidence: 99%
“…This indicates the plasticity of LC differentiation, but the differentiation of mouth mucosal LCs is regulated by epithelial differentiation signals. Several studies have identified that oral mucosal LCs are composed of three distinct subsets, including CD103+LC1, CD11b+LC2, and moLC [65].…”
Section: Characteristics Of Langerhans Cellsmentioning
confidence: 99%